Comparative evaluation of the viscosity and length of resin tags of conventional and hydrophilic pit and fissure sealants on permanent molars: An In vitro study - Jayashri Prabakar; Joseph John; I Meignana Arumugham; R Pradeep Kumar; D Sri Sakthi (Wolters Kluwer Medknow Publications, 2018)
Background: The World Health Organization considers sealing the pit and fissures as a primary preventive measure and is one of the most effective, least invasive means to ensure the complete protection of the occlusal surface from the carious phenomenon. In vitro tests play a vital role in providing the necessary information regarding the efficacy of newer brands of sealants in a short period. Therefore, the aim of the present study was to evaluate and compare the viscosity and length of resin tag of conventional and hydrophilic sealant on permanent molars. Materials and Methods: Twenty extracted third molars were randomly divided into two groups: Group I: Conventional sealant (Clinpro 3M ESPE) and Group II: Hydrophilic sealant (UltraSeal XT Hydro). Occlusal surfaces of each tooth were pretreated with the acid etchant, and the respective sealants were placed. Both the groups were then subjected to thermocycling and sectioned longitudinally. The sectioned tooth specimens were examined under scanning electron microscope for resin tag length measurements. Viscosities were evaluated using an Anton Paar viscometer. Independent t-test was used to compare the difference in mean resin tag length of Group I and Group II sealants. Results: Viscosity measurements of Group I and Group II were found to be 0.9 mega Pascal (MPa) and 0.7 MPa and the mean resin tag length of Group II (10.03 ± 1.00 μm) was found to be higher than Group I (7.46 ± 0.95 μm) and was found to be significant statistically (P = 0.001). Conclusion: Based on the results of the present study, it can be concluded that Group II sealant exhibited lower viscosity and formed resin tag of sufficient length than that of Group I sealants. Therefore, hydrophilic sealant showed better results as compared to a conventional sealant.